ECONOMIC ANALYSIS OF THE IMPACT OF ECONOMIC VARIABLES ON AGRICULTURAL INVESTMENT IN IRAQ FOR THE PERIOD 1990-2020 - Bashar , A. S.; Al-Wasity, R. T. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This research aimed to study the effect of some economic variables (agricultural output, interest rate, agricultural exports, and imports) in determining the volume of agricultural investment in Iraq during the period (1990-2020) by conducting a dynamic econometric analysis of the data collected from its secondary sources. The Error Correction Model (ECM) was employed, and the statistical analysis was performed using EViews 12 software. The results revealed a positive and significant long-term relationship between the explanatory variables and the dependent variable, agricultural investment. Its equilibrium value in the long term is one unit, and 7% of the divergence from the equilibrium between the long term and the short term can be adjusted during the same period. The agricultural domestic product and agricultural exports for the previous year have a significant positive effect on agricultural investments, whereas agricultural imports have a negative sign. There is no effect of the interest rate on agricultural investments. The results also showed that there were no structural changes in the model variables during the study period.